EFEKTIFITAS TRICHODERMA INDIGENUS SULAWESI TENGGARA SEBAGAI BIOFUNGISIDA TERHADAP Colletotrichum sp. SECARA IN- VITRO - GUSNAWATY, HS; TAUFIK, MUHAMMAD; HERMAN, HERMAN (Jurnal Agroteknos, 2014)
This research aimed to determine the effectivity of Trichoderm isolates indigenous of Southeast Sulawesi as biofungicide to Colletotrichum sp in- vitro. This research was carried out in the Laboratory of Agrotechnology, Plant Pathology unit, Faculty of Agriculture, Halu Oleo University. Inhibition effectivity of 11 Trichoderma spp. isolates was done in double PDA media. This research used the complete randomized design (CRD). The observed variables were the inhibitory of Trichoderma spp. indigenous on the growth of Colletotrichum sp. Research result showed that the 11 isolates were effective as biofungicide against Colletotrichum sp. The data analysis showed that isolates DPA was the best isolate, inhibiting Colletotrichum sp. by 77.69%, otherwise LKP was isolate with the lowest inhibitory ability against Colletotrichum sp, by 65.07%. Inhibition mechanism of isolates DPA and DKT against Colletotrichum sp was by area competition and parasitism.Key words: Antagonist, Colletotrichum sp., Trichoderma Indigenous.